2017
DOI: 10.1007/s12020-017-1247-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypersexuality in men with prolactinomas treated with dopamine agonists

Abstract: Prolactinoma is the most common hypersecreting tumor of pituitary gland [1] and medical therapy with dopamine agonists (DAs) is recommended as first line intervention. DA therapy is effective in reversing hyperprolactinemia and its consequences-secondary hypogonadism and galactor-rhea and may induce tumor shrinkage [2]. DA, such as cabergoline and bromocriptine, lead to prolactin normal-ization by acting through D2 receptors on the lactotroph cells. In many cases DA therapy is necessary for extended period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In one of the early case series of DA-induced ICDs in hyperprolactinaemic patients, we proposed the term ‘dopa-testotoxicosis’ to highlight the male predilection and hypersexuality predominance in DA-induced ICDs in the prolactinoma setting ( De Sousa et al 2017 ). This prompted debate in the literature as to the role of testosterone in contributing to hypersexuality in this context ( Bancos et al 2017 , Athanasoulia-Kaspar et al 2018 , Barake et al 2018 , Celik et al 2018 , Dogansen et al 2019 , Ioachimescu et al 2019 ). We subsequently explored this association and other potential risk factors in a large cross-sectional analysis of 113 hyperprolactinaemic patients vs 99 healthy controls.…”
Section: Risks Of Dopamine Agonist Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the early case series of DA-induced ICDs in hyperprolactinaemic patients, we proposed the term ‘dopa-testotoxicosis’ to highlight the male predilection and hypersexuality predominance in DA-induced ICDs in the prolactinoma setting ( De Sousa et al 2017 ). This prompted debate in the literature as to the role of testosterone in contributing to hypersexuality in this context ( Bancos et al 2017 , Athanasoulia-Kaspar et al 2018 , Barake et al 2018 , Celik et al 2018 , Dogansen et al 2019 , Ioachimescu et al 2019 ). We subsequently explored this association and other potential risk factors in a large cross-sectional analysis of 113 hyperprolactinaemic patients vs 99 healthy controls.…”
Section: Risks Of Dopamine Agonist Therapymentioning
confidence: 99%
“…However, aripiprazole also has agonist activity at the D3 receptor, and the aforementioned FDA study found an increased risk of ICDs in aripiprazole-treated individuals ( Moore et al 2014 ). Dose reduction or switching to another DA has also been suggested in the management of DA-induced ICDs as lowering the dose in particular may reduce ICD symptoms ( Bancos et al 2014 , 2017 , De Sousa et al 2017 , Celik et al 2018 , Dogansen et al 2019 ). However, this is not substantiated by other data showing that the risk of ICD development is not associated with DA type or dose ( Martinkova et al 2011 , Bancos et al 2014 , De Sousa et al 2017 , 2019 a , Celik et al 2018 , Dogansen et al 2019 ).…”
Section: Risks Of Dopamine Agonist Therapymentioning
confidence: 99%
“…Irina and Garnik's study supports this, linking joblessness and increased free time to excessive sexual behaviors. Moreover, unemployment may contribute to depression and reduced self-esteem, further elevating the risk of engaging in hypersexuality as a coping mechanism (Bancos, Nippoldt, & Erickson, 2017;Коcharyan, 2019). Among sexual history characteristics, the use of pornography, paraphilic behaviours, and conflict in sex frequency have a positive relationship with CSBD.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors have been identified, such as male gender, young age, and presence of psychiatric comorbidities. Dopamine agonists are also commonly used in the endocrinological setting as a first-line treatment for PRL-secreting adenomas (prolactinomas), although at a much lower dosage (Table 1), [86]. Even at such dosages, however, impulse control disorders may appear: while their prevalence is debated due to different measurement tools, impulse control disorders are significantly more common in prolactinoma/hyperprolactinemia patients treated with dopamine agonists than healthy controls [87].…”
Section: Evidencementioning
confidence: 99%